Metode PjBL: Strategi Pengembangan Modul Ajar Berdiferensiasi untuk Meningkatkan Keaktifan dan Kreativitas Siswa Pada Mata Pelajaran Sejarah - Nur Fuadi, Hilal; Harmanto, Harmanto (Jurnal Pendidikan Madrasah, 2024)
This research aims to develop differentiated teaching modules combined with the project-based learning model to increase students' activeness and creativity in participating in history learning at SMA Negeri 1 Gondang Bojonegoro in the chapter on the Hindu-Buddhist maritime kingdoms in Indonesia. The teaching modules developed will be validated by several experts. The results of this research were that the validation value from material experts obtained a percentage of 82.53% with very appropriate criteria, the validation value from media experts was 78.37% so this teaching module was declared valid. Plus, results the attractiveness test from educators obtained a percentage of 86.80% and from students 88.25% so this teaching module was declared attractive. Based on these results, the differentiated teaching module can be declared suitable for use.